Rancang Bangun E-Helpdesk Kampus Menggunakan Metode Agile - Zidni Ilman Wahyudi; Elvi Rahmi (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Politeknik Negeri Bengkalis, which serves thousands of students, frequently receives complaints regarding facilities and infrastructure, often managed manually through the Student Affairs Department due to the lack of a dedicated campus complaint feature. This traditional method results in unrecorded complaints and slow processing. To address this, an effective and transparent system is necessary to improve service quality and student satisfaction. The purpose of this study is to design and build an E-Helpdesk Campus application for mobile platforms using the Agile development method. The system was developed through two main iterations, focusing on features like complaint submission with categorization, status monitoring, and user management for campus staff/admin. The application was built using the Flutter framework. Based on the results of Black Box Testing, the E-Helpdesk Campus system was successfully implemented and operates effectively, replacing the manual process. The system successfully records complaints in a structured manner, allows students to monitor progress, and is proven to be user-friendly, thereby achieving the research objectives of creating an effective and transparent student complaint system.